Influence of topographic data uncertainties and model resolution on the numerical simulation of lava flows. (February 2019) - Bilotta, Giuseppe; Cappello, Annalisa; Hérault, Alexis; Del Negro, Ciro
Abstract: The emplacement of lava flows is mainly controlled by the topography, which is an essential input parameter to all numerical simulation models. The sensitivity of these models to the uncertainties in topographic data, and the consequent error propagation, may have non-negligible effects on the accuracy and reliability of the modelling of the lava flow hazard. Quantified analysis of the model sensitivity is thus of primary importance in constraining the uncertainty in the prospected lava inundation hazard, with implications for civil protection purposes. We assess the impact of errors, uncertainties and level of detail in topographic data on the lava flow emplacement modelled by the MAGFLOW cellular automaton. We show that the most influential external factors are rheology and vent geolocation, and that increasing the automaton resolution improves the accuracy of simulations, while making them more sensitive to perturbations in topographic data. Highlights: We present a method for model sensitivity analysis to topographic data uncertainties. Rheological parameters influence the model sensitivity. Model resolution affects sensitivity more than data resolution. Georeferencing errors have the highest impact on lava flow emplacement. Up-to-date topographic data is recommended, even if at low spatial resolution.